Product Angular and Rovibrational State Distributions of the Li + HF(v=0, j=0) → LiF(v', j') + H Reaction (Journal of Atomic and Molecular Sciences, 2016)
A state-to-state dynamics analysis of the title reaction has been investigatedvia the quasiclassical trajecory method. Results of the product state resolved differentialcross sections, polarization parameters, as well as rovibrational state distributionswere revealed and discussed, most of which agree well with the recent quantum mechanicsstudy by Roncero and co-workers. It was found that more than 82.28% ofreactive trajectories undergo the direct reaction mechanism. The title reaction occurspredominantly in the head-end collision.